Troska Chrystusa o grzeszny Kościół w Komentarzu do Księgi Sofoniasza św. Hieronima - Bardski, Krzysztof (Collectanea Theologica, 2018)
The first part of the article presents the allegorical interpretation of several passages connected with the sins of the members of the Church according to the Commentary of St. Jerome to the prophet Zephaniah: a. The vain glory and false dignity of priests and bishops (Zeph 1:4); b. The abandonment of Christ’s garments (Zeph 1:8); c. Disrespect for baptism and penance (Zeph 1:10); d. Oppression due to false doctrines (Zeph 1:11, 2:8); e. Sins committed by the representatives of the Church (Zeph 2:9); f. False Christians inside the Church (Zeph 2:14); g. Oppressive superiors (Zeph 3:3); h. Church doctors disregarding the Holy Spirit and the goodness of God. In the second part, the author explores the passages allegorically interpreted in relation to the care of Christ for his beloved Church: a. The light of the word and wisdom (Zeph 1:12); b. Destruction of perverse structures (Zeph 1:13); c. An invitation to communion in love and peace (Zeph 2:1); d. The ”Rest” of those who know the Word of God (Zeph 2:9); e. Commitment to mercy (Zeph 3:10-13); f. The end of the punishment and the gift of joy (Zeph 3:14- 18); g. The promise of eternal glory (Zeph 3:19-20).